Endolaryngeal diode laser surgery for early glottic carcinomas involving anterior commissure - Tuncel, Umit; Kilic, Caner (The European Research Journal, 2017)
Objective. In this study, we present the results of endolaryngeal diode laser surgery in patients with an early stage laryngeal carcinoma involving the anterior commissure (AC). Methods. A total of 108 patients (103 males, five females; mean age: 52.4 years; range; 31 to 75 years) who were treated between January 2010 and January 2015 were included in this study. All patients with glottic cancer had anterior commissure lesions. Complications, recurrence rates, and overall survival associated with diode laser surgery were recorded. Results. Based on the AC classification, the initial local control rate was 89.4% for the AC0 tumors, 81.3% for the AC1 tumors, and 90% for the AC2 tumors. Five-year disease-free and overall survival rates were 93.1% and 98.3, respectively. Conclusion. This study provides evidence that microscopic endolaryngeal diode laser surgery is a safe and effective option for the treatment of early glottic cancer involving the AC.